Analisis Pemeliharaan Alat Medis Oleh Instalasi Pemeliharaan Sarana Rumah Sakit Umum Daerah Petala Bumi Provinsi Riau Tahun 2023: Analysis of Medical Equipment Maintenance by the Facility Maintenance Installation at Petala Bumi Regional General Hospital, Riau Province, in 2023 - RICKY WIRANATA (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
The Hospital Facility Maintenance Installation (IPSRS) at Petala Bumi Regional General Hospital, Pekanbaru, functions under the direct supervision of the Hospital Director and is responsible for maintaining hospital facilities, infrastructure, and medical equipment to ensure safety and service quality. This descriptive-analytic qualitative study (2023) aimed to analyze the medical equipment maintenance system at IPSRS, involving four informants from hospital management and technical staff. Data were obtained through interviews, observations, and document reviews, analyzed using content analysis with triangulation techniques. The findings show that IPSRS faces human resource shortages, with limited staff qualifications and multitasking duties affecting performance. The maintenance budget is available but requires better allocation. Materials and spare parts are mostly sufficient but partly depend on third-party suppliers. SOPs exist but are not fully implemented due to HR constraints and lack of evaluation. The organizational structure functions adequately but needs better HR placement. It is recommended that hospital management add skilled technical staff, update SOPs, and enhance staff competence through training and certification. Strengthening HR, budget management, and maintenance procedures will improve IPSRS efficiency and support high-quality, sustainable hospital services.